Predictors of Pediculosis Capitis among Primary School Children in Kuantan, Pahang - Mohd Tohit, Nor Faiza; Mohd Rus, Razman; Zulkifly , Najhan Anis (IIUM Medical Journal Malaysia, 2020)
Introduction: Pediculosis capitis is a worldwide problem which carries significant consequences among the school children and caregivers. This study aims to investigate the prevalence and predictors of Pediculosis capitis among primary school children in Kuantan, Pahang. Materials and method: An analytical crosssectional study using two-stage cluster random sampling was carried out among 1,365 primary school children in seven schools in Kuantan, Pahang. A selfadministered validated questionnaire was used followed by hair and scalp examination. Results: The median age of the respondents was 8.0 years. Majority of them were males (53.41%), Malays (60.29%), household income between RM1000RM2999 (31.87%) and from urban school location (98.68%). The overall prevalence of Pediculosis capitis was 9.6% (n=131). Multivariate logistic regression analysis showed that predictors for Pediculosis capitis were female (Odds ratio (OR)=8.571, 95% Confidence interval (CI)=5.024-14.620), Indian (OR=5.560, 95% CI=3.384-9.136), those with siblings more than five (OR=2.644, 95% CI=1.044-6.700), history of contact with infested person (OR=2.445, 95% CI=1.619-3.691) and urban school location (OR=0.030, 95% CI=0.284-0.091). Conclusion: Pediculosis capitis is a common public health problem affecting primary schoolchildren in Kuantan, Pahang and those levels are of epidemic importance. Hence, preventive measures are necessary to reduce the transmission of head lice among school children.